KEANEKARAGAMAN TUMBUHAN OBAT MASYARAKAT ADAT KENEGERIAN KOTO ANAU SEBAGAI RANCANGAN MEDIA ELECTRONIC BOOKLET BIOLOGI SMA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning media is one of the factors that can achieve success in a learning process. Indigenous peoples who still maintain traditions in traditional medicine made from plants, is one thing that is very good to be explored and used as a source of reference for learning media in schools. This study aims to determine the types of plants that are used by the indigenous people of the Kenegeriaan Koto Anau as ingredients for traditional medicine, which later the results of this research will be used as a design in making learning media in the form of Electronic Booklets. The research method used is the snowball sampling technique with the resource persons who are traditional officials in the area and traditional healers. The results of the survey and observations carried out, obtained as many as 44 types of medicinal plants from 31 Families with 7 types of Habitus. These results will be used as data for the material description section in the Electronic Booklet design. The design is carried out using the ADDIE model to the Design stage.Key Words: Electronic booklet, Medical Plants, Indigenous Peoples of Koto Anau.